2015
DOI: 10.4103/0972-5229.171390
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between inferior vena cava diameter measurements by subxiphoid versus transhepatic views

Abstract: Context:Correcting hypovolemia is extremely important. Central venous pressure measurement is often done to assess volume status. Measurement of inferior vena cava (IVC) is conventionally done in the subcostal view using ultrasonography. It may not be possible to obtain this view in all patients.Aims:We therefore evaluated the limits of agreement between the IVC diameter measurement and variation in subcostal and that by the lateral transhepatic view.Settings and Design:Prospective study in a tertiary care ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
3
14
0
1
Order By: Relevance
“…We observed a better correlation between the SC and TH views when the F-IVC was above 0.75 than when it was below Previous studies evaluating the TH approach (also called the right lateral or midaxillary approach) concluded that this view could be a surrogate for the SC view in IVC assessment. 9,[11][12][13] As in our study, a correlation was found between the SC and TH views with a low bias in the Bland and Altman analysis. [11][12][13] However, the limits of agreement were always wide, questioning the relevance of the TH view as a surrogate for the SC view.…”
Section: Re Sultssupporting
confidence: 79%
See 3 more Smart Citations
“…We observed a better correlation between the SC and TH views when the F-IVC was above 0.75 than when it was below Previous studies evaluating the TH approach (also called the right lateral or midaxillary approach) concluded that this view could be a surrogate for the SC view in IVC assessment. 9,[11][12][13] As in our study, a correlation was found between the SC and TH views with a low bias in the Bland and Altman analysis. [11][12][13] However, the limits of agreement were always wide, questioning the relevance of the TH view as a surrogate for the SC view.…”
Section: Re Sultssupporting
confidence: 79%
“…9,[11][12][13] As in our study, a correlation was found between the SC and TH views with a low bias in the Bland and Altman analysis. [11][12][13] However, the limits of agreement were always wide, questioning the relevance of the TH view as a surrogate for the SC view. 11,12 In the present study, the limits of agreement found were not clinically acceptable because of an error of approximately 7-8 mm for the IVC diameter measurements.…”
Section: Re Sultssupporting
confidence: 79%
See 2 more Smart Citations
“…Beim schlafenden Neugeborenen sind diese Differenzen des Diameters zwischen Inspiration und Exspiration marginal und die ausschließliche Messung in der Exspirationsphase möglich. Dies wird durch vorliegende Arbeiten bestätigt, wie auch die optimalen Messpunkte, die für die Aorta abdominalis 1 cm vor dem Abgang der Arteria mesenterica superior und für die Vena cava inferior in Höhe des Konfluenz der Venae hepaticae anzustreben sind [11,12,18,19]. Zudem ermöglichen der Längsschnitt und die Einstellung beider Gefäße einen direkten, wenn auch subjektiven visuellen Vergleich der Weite der Gefäße und damit ihrer Füllung.…”
Section: Diskussionunclassified